2015
DOI: 10.2471/blt.14.146951
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to increase the demand for childhood vaccination in low- and middle-income countries: a systematic review and meta-analysis

Abstract: ObjectiveTo investigate which strategies to increase demand for vaccination are effective in increasing child vaccine coverage in low- and middle-income countries.MethodsWe searched MEDLINE, EMBASE, Cochrane library, POPLINE, ECONLIT, CINAHL, LILACS, BDSP, Web of Science and Scopus databases for relevant studies, published in English, French, German, Hindi, Portuguese and Spanish up to 25 March 2014. We included studies of interventions intended to increase demand for routine childhood vaccination. Studies wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 19 publications
2
75
1
Order By: Relevance
“…However, a study conducted in the US reported that parents conforming to the nationally recommended vaccination schedule were more likely to rank internet as the most important source in their networks as compared with non-conformer parents [34]. Current review related to childhood vaccination uptake using internet found similar findings [35][36][37][38].…”
Section: Internet-based Educational Interventionsupporting
confidence: 63%
“…However, a study conducted in the US reported that parents conforming to the nationally recommended vaccination schedule were more likely to rank internet as the most important source in their networks as compared with non-conformer parents [34]. Current review related to childhood vaccination uptake using internet found similar findings [35][36][37][38].…”
Section: Internet-based Educational Interventionsupporting
confidence: 63%
“…Despite varying results among LGAs, the overall survey findings point to both factors of supply and demand in contributing to low vaccination coverage in Nigeria, as seen in other weak health systems [14]. Lack of knowledge or education about vaccines and vaccination services was the most commonly reported reason for non-vaccination, and knowledge about the safety and importance of vaccines were identified as the most important types of information needed to help mothers/caretakers decide to vaccinate their children.…”
Section: Discussionmentioning
confidence: 99%
“…While noting the central importance of vaccine supply and distribution, one review also took into account the demand side and argued that this was important to overcome obstacles that could disadvantage the poorest. The review suggests that both education and financial incentives are effective at increasing use, but places more emphasis on education, and shows that knowledge-based approaches are most important (Johri et al, 2016). Of those strategies seeking to improve vaccination rates, the success of face-to-face interventions aimed at increasing knowledge is low (the review argues for routine vaccination through existing health service activities, not new channels; Kaufman et al, 2013).…”
Section: Interventions To Improve Nutrition and Growthmentioning
confidence: 99%